The effects of mental practice in neurological rehabilitation; a systematic review and meta-analysis - Braun, Susy; Kleynen, Melanie; van Heel, Tessa; Kruithof, Nena; Wade, Derick; Beurskens, Anna (Frontiers in Human Neuroscience, 2013)
Objective: To investigate the beneficial and adverse effects of a mental practice intervention on activities, cognition and emotion in patients after stroke, patients with Parkinson’s disease or multiple sclerosis. Methods: Electronic databases PubMed/Medline, PEDro, Science Direct, Cochrane Library, PsycINFO, Rehadat, Embase, and Picarta were searched until June 2012. Fourteen randomised controlled trials in stroke and two randomised controlled trials in Parkinson’s disease were included, representing 491 patients (421 with stroke). No randomised controlled trials in multiple sclerosis were identified. The methodologic quality of the included trials was assessed with the Amsterdam-Maastricht-Consensus-List (AMCL). Information on study characteristics and outcomes was summarized and evidence for effects described. Data from individual studies in stroke with same outcome measures were pooled. Results: The included 16 randomised controlled trials were heterogeneous and methodologic quality varied. Ten trials reported significant effects in favour of mental practice in patients with stroke (n=9) and Parkinson’s disease (n=1), In six studies mental practice had similar effects as therapy as usual (n=5 in stroke and n=1 in Parkinson’s disease populations). Of six performed meta-analyses with identical measures in stroke studies only two showed significant effects of mental practice: short term improvement of arm-hand-ability (ARAT: SMD 0.62; 95%CI: 0.05 to 1.19) and improvement of performances of activities (NRS: SMD 0.9; 95%CI: 0.04 to 1.77). Five studies found effects on cognition (e.g. effects on attention, plan actions in unfamiliar surroundings) and four reported observed side-effects, both positive (e.g. might increase motivation and arousal and reduce depression) and negative (diminished concentration, irritation). Conclusions: Mental practice might have positive effects on performance of activities in patients with neurological diseases, but this review repo